Grundtvig-selskabets tilblivelse og virksomhed i dets første tiår - Høirup, Henning (Grundtvig-Studier, 1957)
The Origin of the Grundtvig Society and its Activities during its First Decade. By Henning Høirup. The Grundtvig Society was founded on September 8th, 1947, in the Bishop’s Palace at Ribe. Three theological research-workers — Bishop C. I. Scharling, Dr. Villiam Grønbæk and the Reverend Henning Høirup — together with three young historians of literature — William Michelsen, Sten Johansen and Helge Toldberg — had at several private meetings discussed a series of problems of importance for Grundtvigian research. From this sprang the idea of a more comprehensive Society, which could pre-eminently become a forum for the extensive and many-sided activity which was beeing devoted to the study of Grundvig’s life and work. Invitations were therefore sent to all known research-students of Grundtvig to join the new Society, which was constituted at a meeting on January 13th, 1948. It was resolved that the Society should be open to all who were interested, and that a year-book — “Grundtvig- Studier” — should be published. The first President of the Society was Bishop Scharling, D. D.; Helge Toldberg became the Secretary and Henning Høirup the Editor of “Grundtvig-Studier”. The number of members soon rose to about 500. The Society was granted the free use of the Grundtvig Library at Vartov, a centre for study much prized by research workers. Soon the Society was already avtive in investigating the possibilities of a great Collected Edition of Grundtvig’s writings, an edition which should also include the enormous mass of unprinted material which is to be found in the Royal Library and elsewhere in Denmark. The plan was originally put forward by Helge Toldberg and William Michelsen. Preliminary negotiations were carried on with the Ministry of Education, The Carlsberg Fund, and the Danish Language and Literature Society, and as a sort of preparatory task, a partial cataloguing of Grundtvig’s writings was carried out, an experimental piece of work which proved particulary beneficial in creating the possibility of laying down uniform principles for cataloguing. This work was financed by grants from the memorial bequest of L. Zeuthen. One link in the work of making the priceless collections of the Grundtvig Archives available for research consisted of making microfilms of them, a task which was undertaken by the Royal Library and financed by the Library and the Ministry of Education. In addition to “Grundtvig-Studier”, which is published in September each year, the Society began publishing a series of writings, the first of which was Henning Høirup thesis: “Grundtvigs Syn paa Tro og Erkendelse” (“Grundtvig’s Views on Faith and Understanding”) and which in the past ten years has come to include ten separate books. In 1951 the first President of the Society, Bishop Scharling, died, and Dean Henning Høirup, D. D., became his successor, while Dr. Gustav Albeck, Ph. D., took over the post of Editor of “Grundtvig-Studier” . In the same year a very fruitful meeting between Danish and Norwegian workers in the field of Grundtvigian research took place at “Lysebu” near Oslo — a little Grundtvig Congress with a series of lectures which mainly sought to shed light on the central problem: Grundtvig and Norway. Here, too, there was an opportunity to make valuable personal contacts, and to discuss common tasks to be undertaken in the future, e. g., a proposal put forward by Dr. Albeck for a special edition of Grundtvig’s correspondence with prominent Norwegians, covering the whole period from Nordahl Brun in 1809 to Grundtvig’s death in 1872. Every year the Society has arranged a big annual meeting in Copenhagen, Aarhus or Odense, with a general meeting and election of the Executive Committee, and with at least two lectures, which have often been subsequently published in “Grundtvig-Studier“, or in other ways have made their mark in the literature about Grundtvig. The Society has also arranged a number of local meetings (in Aarhus and especially in Copenhagen). Thanks to the establishment of “The General State Fund for the Advancement of Knowledge”, the Society succeeded in 1954 (in close co-operation with the “Danish Language and Literature Society, whose administrator is Dr. Albert Fabritius, Ph. D.) in obtaining the necessary financial support and an adequate organisation for a complete cataloguing of the Grundtvig Archives, with Gustav Albeck, Uffe Hansen, Steen Johansen, William Michelsen, Kai Thaning, Helge Toldberg, K. E. Bugge, and Niels Kofoed as cataloguers, under the professional supervision of Dr. Høirup and Professor Peter Skautrup, Ph. D. Up to the present more than half the Archives have been catalogued. In the course of five years the catalogue will be available in about twenty-five volumes, which will be sold principally to libraries catering for scholars and to other central libraries. Up to now the first three volumes have been published. At the beginning of its second decade the Society can look back on the great contribution which it has already made, and forward to a host of tasks which are still undone, both in the sphere of research and in relation to the Society’s other important task — to spread the knowledge of Grundtvig’s life and ideas both at home and abroad.